Interactive media in Islamic education: Enhancing engagement amid infrastructure challenges at Muhammadiyah 12 Senior High School Jakarta - Pasha, Adinda Sabrina; Rahmanto, Muhammad Arifin (Asatiza: Jurnal Pendidikan, 2025)
This study examines the effects of interactive media (PowerPoint, YouTube, Kahoot, Canva) on student engagement and learning outcomes in Islamic Religious Education (PAI) at Muhammadiyah 12 Senior High School, Jakarta. Employing a qualitative descriptive method, data were collected via semi-structured interviews with two teachers and four students, supplemented by document analysis. Results indicate that 83% of students exhibited heightened motivation and comprehension, particularly through videos and gamification, aligning with the TPACK framework. However, 67% encountered technical barriers (e.g., unstable Wi-Fi, limited data quotas), while teachers noted infrastructural and digital literacy constraints. The study highlights the potential of multimedia to clarify abstract concepts and promote student-centered learning, contingent on addressing technical gaps. Recommendations include institutional investments in Wi-Fi infrastructure, device provision, and teacher training, in line with Indonesia’s Merdeka Belajar policy. It calls for standardized PAI digital resources and digital pedagogy integration in teacher certification. Future research should explore scalability across rural-urban contexts.